Hematological Profile of Bader Fish (Barbonymus altus) in the Brantas River, Blitar Region in Measurement of River Water Quality - Alby Ghifari Azhar; Asus Maizar Suryanto Hertika; Andi Kurniawan (Jurnal Penelitian Pendidikan IPA, 2024)
Brantas River is habitat to a fish species known as the bader fish (Barbonymus altus). Research aims to evaluate the hematological profile of the bader fish as a means to assess the quality of the Brantas River in the Blitar region. Determining the waste flow from community activities that influences blood quality of bader fish is another goal of this research. To achieve this, various water quality indices were measured in the river and hematological parameters measured in the fish. Data collection was conducted once every week for three weeks during 17 January to 17 March 2022. The measurements aimed to observe any changes in the fish's hematological profile over this period. Two data analysis techniques were employed for the research: Pollution Index (IP) and Canonical Correlation Analysis (CCA). IP measurements reveal that all three stations share a common assessment, classifying them as having light pollution. When analyzing correlation measurements through CCA, it was found that erythrocytes exhibited a robust positive correlation with a pH value of 0.549, while conversely, DO (Dissolved Oxygen) showed a strong negative correlation with leukocytes with value -0.717. In summary, the water conditions in the Brantas region remain conducive for the habitat of bader fish.